Effects of a tree row on greenhouse gas fluxes, growing conditions and soil microbial communities on an oat field in Southern Finland - Heimsch, Laura; Huusko, Karoliina; Karhu, Kristiina; Mganga, Kevin Z.; Kalu, Subin; Kulmala, Liisa (Agriculture, ecosystems & environment, 2023)
Agricultural ecosystems are facing critical loss of biodiversity, soil nutrients, and cultural values. Intensive crop production has caused landscape homogenisation, with trees and hedges increasingly disappearing from agricultural land. Changes in farming practices are essential to increase biodiversity and improve soil biogeochemical processes, such as nutrient cycling, soil carbon uptake, and sequestration, as well as to improve the resilience and fertility of farming systems. Agroforestry is an important practice for implementing and improving natural and cultural value of landscapes, but in northern countries, agroforestry methods remain rarely utilised. Our study was conducted in Southern Finland on an agricultural field where a row of willow and alder was planted 6 years prior to our study. We concentrated on the effects of the tree row on crop growing conditions and how far from the trees possible impacts can be observed. We studied soil properties, carbon dioxide (CO2), nitrous oxide (N2O), and methane (CH4) exchange, and soil microbial communities. The impact of trees on crop growing conditions, biomass production, and greenhouse gas fluxes was modest and did not extend further than few meters from the tree row in the warm and dry growing season of 2019. N2O and CH4 fluxes were negligible and the tree row did not increase greenhouse gas emissions from soil. Soil microbial diversity was clearly improved by the presence of trees due to more diverse habitats. The tree row also slightly decreased the estimated annual net emissions of carbon into the atmosphere. Due to positive indications of the effects of agroforestry on biodiversity and carbon uptake, we highly recommend further studies within various agroforestry practices in Nordic countries. •Impact of the tree row on crop growing conditions was modest and extending only to close vicinity of the trees.•Soil microbial diversity was increased by the presence of trees.•Tree row provided additional carbon accumulation to the agroecosystem.